RAPD ANALYSIS IN KABULI CHICKPEA SEED ACCESSIONS - GUPTA, NEHA; BHAGYAWANT, SAMEER SURESH (Innovare Journal of Agricultural Sciences, 2021)
Objective: Random amplified polymorphic deoxyribonucleic acid-polymerase chain reaction (RAPD-PCR) methodology promoted the development of molecular assay system to detect DNA polymorphisms. Analysis of genetic diversity among exclusive Kabuli accessions collected from IIPR, Kanpur, was demanding. Methods: The present study apprised application of RAPD in assessing genetic diversity predominantly in Kabuli chickpea seed accessions. Result: Of the 10 RAPD primers tested, the average number of bands per primer per accession accounted to 9.5. Maximum number of bands scored by the primer OPA-17 was 28 while least number of bands displayed by OPG-04 was 14. Conclusion: The accession KAK-2 exhibited polymorphic among all and therefore diverse. Thus, it can be utilized as one of the parents in future chickpea breeding program.